THE USE OF WALL CHARTS AS MEDIA TO TEACH VOCABULARY - Lilis Patria; Sudarsono Sudarsono; Eni Rosnija (Journal of English Educational Study (JEES), 2020)
The aim of this research was to improve the students’ vocabulary using wall charts as learning media. This is a classroom action research with two cycles. The procedures of each cycle were planning, acting, observing and reflecting. The subjects of this research were 31 students of Learning Group VII of SMP Negeri 2 Belitang Hilir. The data are obtained quantitatively and qualitatively, namely classroom observation, interview, test scores, and questionnaires. This research showed that the students could improve to memorize the vocabulary and its meaning with the help of wall charts. The teacher also could help them correct the spelling and pronunciation. Moreover, the students’ attitude towards the teaching-learning process improved since wall charts increased the students’ interest in learning English vocabulary. It can be seen that in cycle 1 was 67 meanwhile in cycle 2 was 81.9. The research result also showed that wall chart was a good medium for learning English vocabulary with mean value 4.52.